Hubungan antara atribut sensori dan kualitas gula merah tebu: pengaruh pH dan kondisi karamelisasi - Athaya Milda Putri Yuwana; Desiana Nuriza Putri; Noor Harini (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Brown cane sugar is a traditional sugar product manufactured without removing the molasses component. Non-enzymatic browning occurred through Maillard reaction when heated in the caramelization process involving complexes between amino acids and sugar reducer possessing important effects on food properties, such as: nutritional value, color, texture, and taste. This study was conducted to analyze the pH effect and caramelization conditions towards the quality of brown cane sugar and the correlation to sensory properties by Partial Least Squares (PLS) Regression by using four treatments: 440 (40-minute caramelization : 0.3% NaHCO3), 710 (40-minute caramelization : 0.7% NaHCO3), 240 (40-minute caramelization : 0% NaHCO3), and 460 (60-minute caramelization : 0.3% NaHCO3). Water content, ash content, color (L, a*, b*), sensory attributes (color, taste, texture) as well as the level of consumer acceptance were investigated. The results showed that texture was positively correlated with moisture, ash, and b* values. The color intensity and taste were negatively correlated with these parameters but positively correlated with pH. Color intensity was also positively correlated with (L*). A caramelization duration and concentration of NaHCO3 given effected the quality of brown cane sugar. In other words, the longer of caramelization duration, the darker of color (blackish brown), with a slightly soft texture, high water content, and strong caramel flavor. Besides, the higher of the concentration of NaHCO3 given, the brighter of the product with hard and sandy textures, which many consumers preferred.